Review of Pediatric Pheochromocytoma and Paraganglioma - Bholah, Reshma; Bunchman, Timothy Edward (Frontiers in Pediatrics, 2017)
Pheochromocytoma and paraganglioma are rare chromaffin cell tumors which secrete catecholamines and form part of the family of neuroendocrine tumors. Although a rare cause of secondary hypertension in pediatrics, the presentation of hypertension in these patients is characteristic and treatment is definitive. The gold standard for diagnosis is via measurement of plasma free metanephrines, with imaging studies performed for localization, identification of metastatic lesions and for surgical resection. Pre-operative therapy with alpha-blocking agents, beta-blockers and potentially tyrosine hydroxylase inhibitors aid in a safe pre, intra and post-operative course. Pheochromocytoma and paraganglioma are inherited in as much as 80% of pediatric cases and all patients with mutations should be followed closely given the risk of recurrence and malignancy. While the presentation of chromaffin cell tumors has been well described with MEN, NF1 and VHL syndromes, the identification of new gene mutations leading to chromaffin cell tumors at a young age is changing the landscape of how clinicians approach such cases. The Paraganglioma-Pheochromocytoma syndromes (SDHx) comprise familial gene mutations, of which the SDHB gene mutation carries a high rate of malignancy. Since the inheritance rate of such tumors is higher than previously described, genetic screening is recommended in all patients and life-long follow-up for recurrent tumors is a must. A multidisciplinary team approach allows for optimal healthcare delivery in such children. This review serves to provide an overview of pediatric pheochromocytoma and paraganglioma, including updates on the preferred methods of imaging, guidelines on gene testing as well as management of hypertension in such patients.